2006
DOI: 10.1111/j.1365-2842.2005.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 2D and 3D finite element analysis of a restored tooth

Abstract: The finite element method is widely used in dental research. The decision to use two-dimensional (2D) or three-dimensional (3D) modelling is dependent on many interrelated factors. The purpose of the present study was to compare and contrast 2D and 3D finite element analysis (FEA) in investigating the mechanical behaviour of a maxillary premolar restored with a full crown under similar conditions of axial and lateral occlusal loading. The 2D analysis required modelling both a buccolingual and mesiodistal secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 13 publications
(15 reference statements)
1
48
0
2
Order By: Relevance
“…This highlights the importance of geometry changes, which our method accurately captured, to the distribution and magnitude of stress. This occurrence was also observed by Romeed et al (2006) who previously found that changes in the geometry between their 2-D and 3-D models of a restored premolar tooth also affected their displacement and profile stresses. Creating the FE model of the biologically realistic structure (the Biological model) from CT data was a time consuming process compared to the user effort required to generate the compartmentalised geometric model (the Compartment model).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This highlights the importance of geometry changes, which our method accurately captured, to the distribution and magnitude of stress. This occurrence was also observed by Romeed et al (2006) who previously found that changes in the geometry between their 2-D and 3-D models of a restored premolar tooth also affected their displacement and profile stresses. Creating the FE model of the biologically realistic structure (the Biological model) from CT data was a time consuming process compared to the user effort required to generate the compartmentalised geometric model (the Compartment model).…”
Section: Discussionsupporting
confidence: 50%
“…Consequently, the simple 2-D model may have overestimated the distribution and magnitude of stress and hence future vulnerability of algal communities. Here we have developed a set of 3-D FE geometric models to represent different aspects of coralline algae morphology and compared these models with a more biologically accurate 3-D FE model generated from computed tomography (CT) data, allowing us to assess the trade-off between computing time (Andersen and Jones, 2006;Romeed et al, 2006) and the need for an appropriate representation of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Romeed et al (2006), the main differences between the use of 2D and 3D FEM are related to geometric complexity, the purpose of the analysis and the accuracy required in the results. 3D analyses are able to capture more complex geometries more efficiently, but accurate mesh refinement control can be impaired by the greater complexity of the generated model.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 3D models for use in FE analysis have became popular in the study of dental biomechanics, because they allow better understanding of the mechanical and fracture behavior of the dental tissues and structures, providing more realistic and accurate results resembling the actual occurrence in clinics 6) than do the simplified 2D models. Accurate geometry is one of the important keys to successful 3D modeling of both sound and restored teeth in FE analysis.…”
Section: Introductionmentioning
confidence: 99%
“…An FE model with a topological description of geometrical and structural asymmetry can be modeled in either a two-dimensional (2D) or three-dimensional (3D) approach [4][5][6] . Recently, 3D models for use in FE analysis have became popular in the study of dental biomechanics, because they allow better understanding of the mechanical and fracture behavior of the dental tissues and structures, providing more realistic and accurate results resembling the actual occurrence in clinics 6) than do the simplified 2D models.…”
Section: Introductionmentioning
confidence: 99%